Agaricus bisporus stipe fed to dairy heifers: effects on growth performance, immunity and antioxidant capacity, and rumen microbiota - Jia, Peng; Lu, Chunguang; Yang, Xingyu; Jiang, Xueyuan; Lei, Hulong; Lu, Naisheng; Xia, Dong (Frontiers in Veterinary Science, 2025)
IntroductionMushrooms are rich in protein, polysaccharides, and other nutrients as a natural homology of medicine and food species, among which Agaricus bisporus is one of the most widely cultivated and consumed mushrooms worldwide. The mushroom stipe is a by-product of the mushroom industry that can be utilized as a feed resource based on its rich nutritional value. This study examined the effects of Agaricus bisporus stipe (ABS) as a feed additive on growth performance, blood indexes, rumen fermentation parameters, nutrient digestion and utilization, and rumen microbiota of heifers.MethodsTwenty Holstein heifers (268 ± 9.43 d of age) were blocked in 10 groups of 2 heifers according to their live weights and ages, and within each group, the 2 heifers were randomly allocated to 1 of 2 treatments: control diet (CON), control diet plus ABS (ABS, 150 g·DM/animal/d).ResultsHeifers supplemented with ABS had higher average daily gain and a tendency to decrease feed conversion ratio, but rumen fermentation parameters were similar between the two treatments. Heifers in ABS had increased IgG, IgA, IgM, SOD, T-AOC, and GSH-Px concentrations while decreasing MDA concentration than heifers in CON. Although energy and nitrogen utilization were similar between treatments, the apparent total-tract digestibilities of NDF and ADF were higher for ABS than for CON heifers. Feeding ABS increased the relative abundance of one phylum (Verrucomicrobiota), two genera (Akkermansia and Ligilactobacillus), and two species (Akkermansia muciniphila and Ligilactobacillus murinus) in the rumen of heifers.DiscussionIn conclusion, heifers receiving ABS have greater growth performance, improved serum immune and antioxidant indexes, increased the relative abundance of some rumen bacteria, and higher nutrient digestion than CON heifers.